Wisatawan Milenial Di Bali - Parhusip, Nina Ester; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA, 2019)
Nowadays travel is dominated by millenial generation, millenial generation is the first generation which grow in digital environment or digital native. The purpose of this study is to explore the factors which influence travel of millennial generation. The main topic discussed in this study is general characteristic of the millenial travel in Bali, the motivation and meaning of travel. The topic discussed in this study show that millenial generation unlike the previous generation when traveling, showing millennial generation have their own travel characteristics and different technologies, play a massive role in travel choices. This research is a descriptive quantitative and descriptive qualitative research. Quantitative research is conducted to determine the characteristics and motivation of millenial tourists by using frequency analysis. Qualitative research is used to know the meaning of travel after a tour. This study used 100 respondents representing the characteristics and motivation of millennial tourists in Bali and semi structured interview with 6 people to know the meaning of millenial generation travel in Bali, as well as techniques of determining informants using Accidental Sampling. The result of this research, that technology is very important for the millennial generation when traveling. The results found that 73% of millennial tourists prefer spend money for a trip to materialistic ownership. The motivation to look for something and attractive, culture and other uniqueness is the highest recorded. The meaning of travel which tourists get is a human right, fundamental needs, health, soul development and education. Most of millennials tell their journey in Bali as an unforgettable experience of culture, nature and other uniqueness.   Keywords : Millenial Tourist, Characteristics, Motivation, and  Personal Meaning